Study on Behaviour of Stud Type Shear Connector in Composite Beam Using ANSYS - Subramani, T; Periasamy, A (International Journal of Engineering and Technology, 2018)
Composite plays a vital role in replacing the existing mild steel in reinforcement and exterior truss structure. This study proposed to design shear connector for joining concrete slab and steel section. Shear connectors has analyzed and predict the best connector for a particular composite beam with respect to static load and the amount of steel in the connector as a common aspect. The use of composite structures is increasingly present in civil construction works nowadays. Composite beams, especially, are structures which include substances, a metal phase placed in particular inside the tension region and a concrete phase, positioned in the compression go sectional location, both are related with the aid of steel gadgets called shear connectors. The main features of this connector are to permit the weight for the joint the beam-column, to restriction longitudinal slipping and uplifting on the factors interface the shear forces. Our project paper presents 3D numerical models of steel-concrete composite beams to simulate their structural behaviour, with emphasis on the beam column interface using Simulations software ANSYS 18.1 based on the Finite Element Method. Mostly these type of structures are widely used in the dynamic loading structures like bridges and high rise buildings. Â Â